Health Communication Strategy in Changing Community Nutrition Behavior and Reducing Stunting Cases in South Konawe Regency, Southeast Sulawesi - Gemiharto, Ilham; Matsumoto, Seira; Molefe , Zanele (Yayasan Ilomata, 2024)
This study aims to analyze the communication capacity of public health cadres in designing and implementing effective health communication campaigns and their impact on changing the nutritional behavior of rural communities and helping to reduce the number of stunting cases in Indonesia. This study uses a qualitative and case study approach focusing on health communication strategies implemented by community health cadres in South Konawe Regency, Southeast Sulawesi Province. Data collection used an in-depth interview method with public health cadres, which included evaluating their understanding of health communication, the use of social media in delivering health messages, and their ability to adapt nutrition messages to the local cultural context. Research findings show that most health cadres do not understand effective health communication. The use of social media in delivering health messages is still not optimal, and there are challenges in understanding and integrating local cultural contexts in nutrition counseling. The implications of this study suggest that enhancing the capacity of community health cadres in South Konawe Regency is imperative, particularly in proficient health communication through social media platforms and understanding the nuances of local cultural contexts. It is anticipated that implementing strategies aimed at augmenting the training and skill development of health cadres would significantly contribute to endeavors to mitigate the prevalence of stunting cases in rural Indonesian regions.